Porous Adsorption Materials for Carbon Dioxide Capture in Industrial Flue Gas - Zeng, Hongxue; Qu, Xinghong; Xu, Dong; Luo, Yang (Frontiers in Chemistry, 2022)
Due to the intensification of the greenhouse effect and the emphasis on the utilization of CO2 resources, the enrichment and separation of CO2 have become a current research focus in the environment and energy. Compared with other technologies, pressure swing adsorption has the advantages of low cost and high efficiency and has been widely used. The design and preparation of high-efficiency adsorbents is the core of the pressure swing adsorption technology. Therefore, high-performance porous CO2 adsorption materials have attracted increasing attention. Porous adsorption materials with high specific surface area, high CO2 adsorption capacity, low regeneration energy, good cycle performance, and moisture resistance have been focused on. This article summarizes the optimization of CO2 adsorption by porous adsorption materials and then applies them to the field of CO2 adsorption. The internal laws between the pore structure, surface chemistry, and CO2 adsorption performance of porous adsorbent materials are discussed. Further development requirements and research focus on porous adsorbent materials for CO2 treatment in industrial waste gas are prospected. The structural design of porous carbon adsorption materials is still the current research focus. With the requirements of applications and environmental conditions, the integrity, mechanical strength and water resistance of high-performance materials need to be met.